Developing tools to study the interaction between the lipopeptide surfactin and phospholipid bicelles with infrared spectroscopy - Blaser, Jennifer M., author; Krummel, Amber, advisor; Levinger, Nancy, committee member; Kipper, Matthew, committee member (Colorado State University. Libraries, 2012)
Surfactin has been shown to have concentration-dependent effects on lipid membranes with proposed mechanisms of action including ion chelation, ion channel formation, and a detergent-like effect. The concentration ranges for these behaviors have not been established, the structure of surfactin in a membrane has not been determined, and information regarding the dynamics of the surfactin-lipid interaction is limited at best. Therefore, a tunable phospholipid bicelle system was created to study the surfactin-lipid interaction as a function of surfactin concentration using infrared (IR) spectroscopy which can provide both structural and dynamic information. But first, the direct interaction between surfactin and bicelles was confirmed with dynamic light scattering (DLS) measurements that suggest surfactin exhibits detergent-like effects above a 2.0 mM concentration. For surfactin in Tris buffer, the IR spectra displayed a significant concentration-dependent shift in the amide-I band and a distinct change in the amide-I to amide-II band intensity ratio. These data indicate that surfactin experiences a conformational transition over the concentration range studied. The conformational transition may occur due to the formation of surfactin micelles and higher order aggregates upon increasing concentration. Surfactin was also studied in the presence of phospholipid bicelles. At low surfactin concentrations in the presence of bicelles, the amide-I band exhibits nearly identical spectral features to those found for higher concentrations of surfactin in Tris buffer, and the amide-I to amide-II band intensity ratios showed similar trends. The results of these studies indicate that the conformation of surfactin may be similar in micelles, higher order aggregates, and bicelles with the bicelles limiting the conformational distribution of the surfactin molecules. Additional studies are necessary to determine surfactin's structure in these model membranes and obtain dynamic information to better understand the mechanism of the surfactin-lipid interaction.
Keywords: bicelles; surfactin; spectroscopy